The most frequent comorbidities at patients with the chronic obstructive pulmonary disease - Krdžić Biljana; Milovanović Jelena; Šipić Maja; Petković Zlatica; Nedeljković Biserka (Praxis Medica, 2018)
Chronic obstructive pulmonary disease (COPD) is a disease with periods of remission and exacerbation and consequential defect of the pulmonary function. It is estimated that around 3 million people die from it annually and predicted that until 2030 the number of deaths will be up to 6 million per year. According to the reports of the World Health Organization and Global initiative for chronic obstructive lung disease (GOLD) it is predicted that COPD in the next decade will be the third leading cause of death in the world.[ 1, 2 ] It is characterized by limited air flow in the breathing pathways which is not completely reversible to therapy. Since there are systemic inflammations at COPD, the mechanisms of the processes have consequences outside the lungs also. Comorbidities are frequent at patients with the Chronic obstructive lung disease and they affect the disease prognosis substantially. The most common comorbidities are cardiovascular diseases, metabolic syndrome, diabetes, anemia, osteoporosis, anxiety and depression, pulmonary embolism.